Tuberculosis [ laboratory diagnosis and treatment strategies - McHugh, Timothy D. [ (Timothy Daniel)] (Advances in molecular and cellular microbiology, 2013)
Tuberculosis is a global health threat and the unique features of Mycobacterium tuberculosis and emergence of drug-resistant strains highlight the challenge it presents. Covering a wealth of state-of-the-art knowledge from active international experts, this book captures the latest developments in the advent of bacteriological, immunological and molecular tools for diagnosis and the development of new drugs. It shows how the challenge of tuberculosis is currently being met, providing insight into the evidence base underlying new developments in diagnosis, drug development and treatment